CURRENT MIGRATIONS INTO COASTAL ZONES OF BENIN: MOTIVES, ECOLOGICAL CONSEQUENCES AND SOCIAL REALITIES - Oscar TEKA; Romeo Brice K. CHABI; Mosunmola Lydia ADELEKE Mosunmola Lydia ADELEKE; Joachim VOGT; Caroline KRAMER; Brice SINSIN (European Journal of Geography)
The main objective of this study is to analyze the migration into the coastal area of Benin and the related possible effects on the socio-economic and ecological environment. In total, 660 coastal household chiefs comprising 262 women and 405 men were interviewed. Semi-structured interviews were made with 32 notables and local authorities of the coastal Districts. The Analysis of Variance was applied in order to test the relationship between socio-demographic parameters and migration motives. Results showed that migrants are above people at working age. The gender offers a possibility of differentiated analysis. The searching for jobs and training and family reasons are the main motives for migration into the coastal area. There is no significant relationship between ethnic groups and types of motivation (P=0.54). But there was a significant relationship between marital status and type of motivation (P=0.00). There is a significant relationship between gender and type of motivation (P<0.00).